Comparison of efficacy of physiotherapy and Taijiquan in elderly patients with knee osteoarthritis - Tian, Zhanwei; Cao, Yafang (The Journal of the International Society of Chinese Health Practices, 2024)
Abstract: Objective: According to the data released by the Statistical Bulletin of National Economic and Social Development 2018 by the Chinese Bureau of Statistics, as of 2018, the number of people aged 60 and above in China reached 249.49 million, accounting for 17.9% of China's total population, and this number is recent years, the incidence of knee osteoarthritis has been increasing year by year. Knee joint osteoarthritis has a significant impact on the living conditions of middle-aged and elderly people in our country and has caused a great economic and social burden on society and families. International guidelines also state that exercise therapy is the preferred approach for patients with milder knee osteoarthritis. Therefore, exercise therapy is given top priority in community health care. Due to decreased physical function among middle-aged and elderly individuals, it is necessary to develop a fitness plan specifically designed for elderly patients with knee arthritis. Taijiquan is considered as low-intensity aerobic exercise suitable for middle-aged and elderly individuals in China. By observing its influence on elderly patients with knee osteoarthritis compared to physical therapy, this paper aims to determine differences in efficacy between Taijiquan practice and physical therapy in improving symptoms associated with knee osteoarthritis among older adults. Methods: 60 elderly patients with knee arthritis were randomly divided into Taijiquan group (n=30) and physical therapy group (n=30). Taijiquan group adopts the "Eight forms of Taijiquan" formulated by the General Administration of Sport of the State. The main movements are: finger curl, lap lap, wild horse hair parting, cloud hand, golden rooster independent, foot pushing, holding the tail of the bird, cross hand, and the rising and folding style. Using progress, retreat, oblique step and center of gravity change in different directions to promote the movement of leg muscles and knee joints to enhance muscle strength and enhance the dynamic stability of the trunk and lower limbs. Perform 60 minutes of exercise three times a week; The physical therapy group performed quadriceps isometric contraction training, straight leg elevation training, knee flexion and extension training three times a week according to the expert consensus of Osteoarthritis Rehabilitation Treatment. Both groups received knee osteoarthritis related health education, including how to correctly exercise and change bad lifestyle habits, once a week for 12 weeks. WOMAC Index (Western Ontario and McMaster University Osteoarthritis Index), joint range of motion and SAS scale (Self-Rating Anxiety) were evaluated before intervention (baseline) and after intervention Scale, the Pittsburgh Sleep Quality Index and the General Self-efficacy Scale. Data were analyzed using Microsoft Excel 2019 and IBM SPSS Statistics 20.0. Continuous variables such as age, BMI and WOMAC score were represented by mean ± standard deviation. A single sample T-test was used to compare the Tai Chi group with the physical therapy group. Chi-square test was used to analyze categorical variables (such as gender, marital status, smoking, alcohol consumption, etc.) between the two groups. For the data that do not meet the normal distribution, non-parametric test is used for statistical analysis. The main indicator of this study was to measure the differences in WOMAC scores and ROM scores between the two groups before and after the intervention. P < 0.05 in all analyses indicated that the indicator was statistically significant. Results: After 12 weeks of intervention, WOMAC score, SAS score and PSQI score of KOA patients in Tai Chi group and physical therapy group were decreased, joint range of motion was increased, GSES score was increased, and symptoms were improved in both groups. However, in the comparative study of the two groups, it was found that the effect of Taijiquan group was significantly better than that of the control group, and the WOMAC score, joint range of motion and SAS score of Taijiquan group were significantly better than that of the physical therapy group, with statistical differences (P < 0.05). No significant differences were found in other indicators, indicating that the effect of Taijiquan group was better than that of the physical therapy group. This study also found that the adherence of the Taijiquan group was higher than that of the physical therapy group, and the overall efficacy perception of the Taijiquan group was significantly better than the latter. Taijiquan is a team sport, and the interaction during practice can promote the interest and enthusiasm of the practitioners. On the other hand, physical therapy requires patients to actively communicate with therapists and actively cooperate with training. The intervention lasting for 3 months is difficult for subjects. Conclusion: The effect of Taijiquan and physical therapy on the symptoms of KOA patients; the influence of Taijiquan and physiotherapy on joint range of motion in patients with KOA and the effects of Taijiquan and physical therapy on the anxiety of KOA patients were analyzed. The study found that after 12 weeks of intervention, the Taijiquan group and the physical therapy group had improved the pain, function, joint motion and anxiety scores of the knee joint, but in general, the effect of Taijiquan group was significantly better than that of the physical therapy group, and the taijiquan group could increase the knee joint motion, relieve stiffness and promote coordinated development of the whole body. There were no serious adverse reactions in the two groups during the study. Compared with physical therapy, Taijiquan group has the characteristics of economy, practicality and convenience, which can increase the treatment compliance of patients with knee osteoarthritis and promote the physical and mental health development of patients with knee osteoarthritis. Taijiquan practice can significantly improve the symptoms of elderly patients with knee arthritis, and compared with physical therapy, Taijiquan practice is better for elderly patients with knee osteoarthritis. Therefore, Taijiquan practice is safe, feasible and effective for knee osteoarthritis in the community. Taijiquan can become a long-term exercise method for the rehabilitation of elderly patients with knee arthritis, and Taijiquan practice is worth promoting and applying in the community.